Arousal Rules: An Empirical Investigation into the Aesthetic Experience of Cross-Modal Perception with Emotional Visual Music - Lee, Irene Eunyoung; Latchoumane, Charles-Francois V.; Jeong, Jaeseung (Frontiers in Psychology, 2017)
Emotional visual music is a promising tool for the study of aesthetic perception in human psychology; however, the production of such stimuli and the mechanisms of auditory-visual emotion perception remain poorly understood. In Experiment 1, we suggested a literature-based, directive approach to emotional visual music design, and inspected the emotional meanings thereof using the self-rated psychometric and electroencephalographic (EEG) responses of the viewers. A two-dimensional (2D) approach to the assessment of emotion (the valence-arousal plane) with frontal alpha power asymmetry EEG (as a proposed index of valence) validated our visual music as an emotional stimulus. In Experiment 2, we used our synthetic stimuli to investigate possible underlying mechanisms of affective evaluation mechanisms in relation to audio and visual integration conditions between modalities (namely congruent, complementation, or incongruent combinations). In this experiment, we found that, when arousal information between auditory and visual modalities was contradictory (for example, active (+) on the audio channel but passive (-) on the video channel), the perceived emotion of cross-modal perception (visual music) followed the channel conveying the stronger arousal. Moreover, we found that an enhancement effect (heightened and compacted in subjects’ emotional responses) in the aesthetic perception of visual music might occur when the two channels contained contradictory arousal information and positive congruency in valence and texture/control. To the best of our knowledge, this work is the first to propose a literature-based directive production of emotional visual music prototypes and the validations thereof for the study of cross-modally evoked aesthetic experiences in human subjects.